Investigation of Growth and Ginsenoside Content of Wild-Simulated Ginseng Cultivated in Different Vegetation Environments for Establishing a Plant Growth Model - Yeong-Bae Yun; Myeongbin Park; Yi Lee; Yurry Um (Plants)
Wild-simulated ginseng (WSG, Panax ginseng C.A. Meyer) is one of the most valuable medicinal plants in the world. This study aimed to investigate the correlation between growth and ginsenoside content of WSG in two different cultivation environments: coniferous and mixed forests. The results showed that air temperature, soil moisture content, and solar radiation were higher in mixed forest than in coniferous forest. Regarding soil properties, electrical conductivity, organic matter, total nitrogen, exchangeable potassium, and magnesium were higher in mixed forest than in coniferous forest. However, exchangeable sodium was lower in mixed forest than in coniferous forest. The analysis of growth characteristics revealed that the number of leaflets was significantly higher in WSG cultivated in mixed forest than in WSG cultivated in coniferous forest, whereas rhizome length, root diameter, root weight, and dry weight were significantly higher in coniferous forest. In contrast, total ginsenoside content and the content of each ginsenoside were much higher in WSG cultivated in mixed forest than in WSG cultivated in coniferous forest. The growth of WSG showed significantly positive correlations with electrical conductivity, organic matter, total nitrogen, exchangeable cations (K+, Mg2+, Na+), and cation exchange capacity. The number of leaflets per stem showed significantly positive correlations with six ginsenosides, whereas petiole length showed significantly negative correlations with mRb1, mRc, and Rb1. In conclusion, growth characteristics of WSG were higher in coniferous forest, but ginsenoside contents were higher in mixed forest. These results might be helpful for establishing the most optimal growth model of WSG, which is affected by various environmental factors.